Theory and methods in political science. - Lowndes, Vivien; Marsh, David, 1946-; Stoker, Gerry (Political analysis., 2018)
Now with substantial extra coverage of methodological issues and an additional chapter on the philosophy of politics, this widely-used text introduces students to the approaches and methods of political science.